Association between Single-Nucleotide Polymorphism in MicroRNA Target Site of DDB2 and Risk of Hepatocellular Carcinoma in a Southern Chinese Population. (8th February 2020) - Qiu, Moqin; Liu, Yingchun; Zhou, Zihan; Jiang, Yanji; Lin, Qiuling; Huo, Rongrui; Liang, Xiumei; Yu, Xiangyuan; Zhou, Xianguo; Yu, Hongping
Abstract : Damage-specific DNA-binding protein 2 (DDB2) is a DNA repair protein mainly involved in nucleotide excision repair, which plays a pivotal role in maintaining genomic stability. In this study, we evaluated the association of single-nucleotide polymorphism (SNP) rs1050244 in miRNA target site of DDB2 gene with risk of hepatocellular carcinoma (HCC) among 1073 HCC patients and 1119 cancer-free controls in a southern Chinese population. Our results showed that no statistically significant association was found between DDB2 rs1050244 and HCC risk. In further analysis stratified by age, sex, smoking, alcohol drinking, and HBV infection status, we found that individuals carrying the CT/TT genotypes of SNP rs1050244 had a significantly decreased risk of HCC compared with those with the CC genotype among non-HBV infected population (adjusted OR = 0.31, 95% CI = 0.13–0.72), and a significant interaction was found between this SNP and HBV infection (P interaction = 0.002 ). Our results suggested that the DDB2 rs1050244 C>T polymorphism was associated with the decreased risk of HCC among non-HBV infected population. Further studies with larger sample sizes are needed to validate our findings.